The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1007/s00204-005-0684-2
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of styrene inhalation on the neuroendocrinological system of rats and the different effects in male and female rats

Abstract: There have been several epidemiological and experimental studies about styrene from the neuroendocrinological viewpoint. Some reported that styrene exposure affected the neuroendocrinological system and enhanced prolactin (PRL) secretion, but others have denied those effects. It was assumed that styrene exposure caused depletion of dopamine (DA), which is a PRL inhibitor, and that, in consequence, the PRL level increased. However, not only DA but also many other factors control PRL secretion. Therefore, the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The only known physiological function of prolactin is the stimulation of milk production and many normal stress situations may lead to elevations without any chemical exposure (Theorell et al 1990). Although screening or guideline studies do not exist for experimental verification of the human observations, mechanistic studies in animal on dopamine, the prolactin-regulating neurotransmitter, do not support an explanation of how styrene may affect prolactin levels (Gagnaire et al 2006;Jarry et al 2002;Umemura et al 2005). Therefore, given the lack of a plausible mechanistic explanation, coupled with the nature of the changes, unspecific acute workplace-related stress is a possible alternative explanation to styrene exposure in these workers.…”
Section: Non-cancer Health Effectsmentioning
confidence: 99%
“…The only known physiological function of prolactin is the stimulation of milk production and many normal stress situations may lead to elevations without any chemical exposure (Theorell et al 1990). Although screening or guideline studies do not exist for experimental verification of the human observations, mechanistic studies in animal on dopamine, the prolactin-regulating neurotransmitter, do not support an explanation of how styrene may affect prolactin levels (Gagnaire et al 2006;Jarry et al 2002;Umemura et al 2005). Therefore, given the lack of a plausible mechanistic explanation, coupled with the nature of the changes, unspecific acute workplace-related stress is a possible alternative explanation to styrene exposure in these workers.…”
Section: Non-cancer Health Effectsmentioning
confidence: 99%
“…In fact, prolactin can be increased by exposure to lead (Govoni et al 1987;Lucchini et al 2000), organic mercury (Carta et al 2003), and manganese (Ellingsen et al 2003;Smargiassi and Mutti 1999;Takser et al 2004), but it can be decreased by exposure to inorganic mercury Lucchini et al 2003;Ramalingam et al 2003), alluminum (Alessio et al 1989), and cadmium (Calderoni et al 2005;). Subjects exposed to chemicals such as styrene (Bergamaschi et al 1996;Luderer et al 2004;Umemura et al 2005), perchloroethylene (Beliles 2002;Ferroni 1992), and anesthetic gases (Lucchini et al 1996;(Marana et al 2003) have shown an increase of serum prolactin, whereas polychlorinated biphenyls (De Krey et al 1994) Possible mechanisms, other than direct effects at the cellular level, may be related to different neurotransmitters involved in the modulation of prolactin secretion. For example, the dopaminergic and serotoninergic systems, respectively, are involved in the physiologic regulation of this hormone as a tonic inhibitor and as an excitatory modulator.…”
Section: Prolactin Changes As a Consequence Of Chemical Exposurementioning
confidence: 99%
“…Increases in serum growth hormone and TSH were also observed and were associated with biomarkers of styrene exposure (13)(14)(15)(16). Toxicological studies on rats also support prolactin secretion as a styrene target, with sex-related differences (17). An up-to-date, comprehensive review of health effects and exposure to styrene is available (18).…”
Section: Introductionmentioning
confidence: 99%